2006
DOI: 10.1002/adma.200502528
|View full text |Cite
|
Sign up to set email alerts
|

Spinning and Processing Continuous Yarns from 4‐Inch Wafer Scale Super‐Aligned Carbon Nanotube Arrays

Abstract: A flexible and elastic carbon coil (see figure) has been fabricated using a continuous yarn of carbon nanotube arrays. The processed yarn is both elastic and pliable and can be freely manipulated and molded to any desired shape that is retained after heat treatment. Owing to their highly ordered macroscopic structures, the good electrical and thermal conductivity of the nanotube components, and their good mechanical properties, these carbon nanostructures may find extensive use in a wide range of applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
424
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 575 publications
(443 citation statements)
references
References 22 publications
9
424
0
2
Order By: Relevance
“…For example, prior to 2007, the reported tensile strengths of continuous CNT fibers without a coagulant lay in the range from 0.4 to 1.2 GPa, no matter if they were spun from a suspension. [5][6][7][8][9][10][11][12] Recently, Windle et al reported the synthesis of continuous high-performance CNT fibers with the highest strength value of 9 GPa. [12] This encouraging breakthrough enlightens the use of macroscale CNTs fibers as a structural reinforcement for many applications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, prior to 2007, the reported tensile strengths of continuous CNT fibers without a coagulant lay in the range from 0.4 to 1.2 GPa, no matter if they were spun from a suspension. [5][6][7][8][9][10][11][12] Recently, Windle et al reported the synthesis of continuous high-performance CNT fibers with the highest strength value of 9 GPa. [12] This encouraging breakthrough enlightens the use of macroscale CNTs fibers as a structural reinforcement for many applications.…”
mentioning
confidence: 99%
“…Figure 1 shows a typical twisting process. Compared with the existing spinning methods developed by other groups, [5][6][7][8][9][10][11] our twisting method may not be suitable for continuous production of CNT fibers, but the control of the diameters and twisting degrees is more convenient. So the fabricated fibers are ideal systems for the study of CNT macroarchitectures.…”
mentioning
confidence: 99%
“…Due to their high-purity, high-quality and ordered structure, the superaligned CNT arrays can be converted into continuous fibers or sheets in the dry state [2,10,11,[14][15][16][17][18]. These fibers and sheets, within which the nanotubes possess a high degree of alignment, have also been incorporated into polymer matrices to make strong CNT/polymer composite fibers [19][20][21].…”
mentioning
confidence: 99%
“…13). The second method is spinning from vertically aligned CNT arrays [14][15][16] . Introducing twisting 15 , tension 17,18 or liquid shrinking during drawing 16,19 aligns and/or compacts the CNTs.…”
mentioning
confidence: 99%
“…The second method is spinning from vertically aligned CNT arrays [14][15][16] . Introducing twisting 15 , tension 17,18 or liquid shrinking during drawing 16,19 aligns and/or compacts the CNTs. Post treatment of twisting led to 1.9 GPa for s b , 7% for d and 4.1 Â 10 2 S cm À 1 for k 20 , but that of twistless rubbing resulted in a porous structure in the fibre 21 .…”
mentioning
confidence: 99%